2011
DOI: 10.4049/jimmunol.1101970
|View full text |Cite
|
Sign up to set email alerts
|

Insights into HLA-Restricted T Cell Responses in a Novel Mouse Model of Dengue Virus Infection Point toward New Implications for Vaccine Design

Abstract: The frequency of dengue virus (DENV) infection has increased dramatically in the last few decades, and the lack of a vaccine has led to significant morbidity and mortality worldwide. To date, a convenient murine system to study human T cell responses to DENV has not been available. Mice transgenic for human leukocyte antigens (HLA) are widely used to model human immune responses and it has been shown that mouse-passaged DENV is able to replicate to significant levels in IFN-α/βR−/− mice. To cover a wide range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
114
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 82 publications
4
114
0
Order By: Relevance
“…Enzyme-linked immunospot (ELISPOT) assays were performed as described previously (35). For CD4 T cell intracellular cytokine staining (ICCS) of spleen, liver, or lung cells, 1 ϫ 10 6 cells were incubated with 5 g/ml of m53 285-299 or m78 417-431 15-mer peptides for 8 h or treated with phorbol myristate acetate (PMA) (100 ng/ml) and ionomycin (500 ng/ml) for 5 h in the presence of brefeldin A (2 g/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme-linked immunospot (ELISPOT) assays were performed as described previously (35). For CD4 T cell intracellular cytokine staining (ICCS) of spleen, liver, or lung cells, 1 ϫ 10 6 cells were incubated with 5 g/ml of m53 285-299 or m78 417-431 15-mer peptides for 8 h or treated with phorbol myristate acetate (PMA) (100 ng/ml) and ionomycin (500 ng/ml) for 5 h in the presence of brefeldin A (2 g/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps DENV's extreme susceptibility to the murine type I IFN-signaling pathway (33,34), the molecules of which differ sufficiently from human analogues to prevent DENV-mediated inhibition (3), limits extraneural antigen availability and results in a blunted cellular immune response. Accordingly, we have observed that the breadth and magnitude of DENV-specific T cell responses in wild-type mice are lower than in IFN-␣/␤ receptor-deficient mice (45,48,50). Combined with the immune-privileged status of the CNS and the capacity of DENV for infection of the CNS, a blunted T cell response may favor efficient DENV replication in the CNS.…”
Section: Discussionmentioning
confidence: 96%
“…Mice transgenic for HLA are widely used to study T cell responses restricted by human major histocompatibility complex (MHC) molecules (16)(17)(18), and it has been shown that mice lacking the alpha/beta interferon receptor (IFN-␣/␤R) support a productive DENV infection (19)(20)(21)(22). To cover a wide range of HLA phenotypes, we backcrossed IFN-␣/␤R Ϫ/Ϫ mice with HLA A*0201, A*0101, B*0701, B*4001, and DRB1*0101 single-alleletransgenic mice.…”
mentioning
confidence: 99%